Impact of Implementing Checklist Management Combined with SOP on Nursing Quality Among ENT Surgery Nurses - Ren L; Han L; Ping F; Yin Y; Liang T; Wang F (Risk Management and Healthcare Policy, 2025)
Liyan Ren,1 Li Han,2 Fumin Ping,3 Yanli Yin,4 Tao Liang,5 Fang Wang6 1Operation Room, Affiliated Hospital of Hebei University of Engineering, Handan, 056002, People’s Republic of China; 2Department of Nephrology, Affiliated Hospital of Hebei University of Engineering, Handan, 056002, People’s Republic of China; 3Affiliated Hospital of Hebei University of Engineering, Handan, 056002, People’s Republic of China; 4Department of Breast Surgery, Affiliated Hospital of Hebei University of Engineering, Handan, 056002, People’s Republic of China; 5Department of Respiratory, Affiliated Hospital of Hebei University of Engineering, Handan, 056002, People’s Republic of China; 6Nursing Department, Affiliated Hospital of Hebei University of Engineering, Handan, 056002, People’s Republic of ChinaCorrespondence: Fang Wang, Email xowu842@163.comObjective: Ear, nose and throat (ENT) surgeries require meticulous nursing care due to their complexity and risk of complications. Traditional nursing models often lack the standardization needed to ensure consistent quality and patient safety. This study aimed to explore the application and effectiveness of checklist management combined with Standard Operating Procedures (SOP) in ENT surgery nursing and its impact on nursing quality improvement.Methods: This was an experimental study using a pretest-posttest control group design. A total of 200 patients undergoing ENT surgery in the Otolaryngology Department of our hospital from April 2023 to April 2024 were randomly divided into control group and intervention group, including 100 cases in each group. The control group received conventional nursing management, while the intervention group was subjected to checklist management combined with SOP. The intervention outcomes, nursing quality scores, and incidence of surgery-related adverse events were compared between the two groups.Results: The baseline characteristics of the two groups showed no significant differences, indicating comparability (P> 0.05). After the nursing intervention, the intervention group demonstrated better outcomes than the control group, with lower Tinnitus Handicap Inventory (THI) scores (P< 0.05). The intervention group also showed higher General Comfort Questionnaire (GCQ) scores, indicating better comfort levels (P< 0.05). The incidence of device-related adverse events in the intervention group was significantly lower than that in the control group (P< 0.05). Additionally, the intervention group had higher physician satisfaction scores (P< 0.05), higher patient satisfaction scores (P< 0.05), better management effectiveness scores (P< 0.05), and significantly improved nursing quality scores compared to the control group (P< 0.05).Conclusion: Checklist management combined with SOP demonstrates excellent effectiveness in ENT surgery nursing, enhancing patient comfort and satisfaction, significantly improving nursing quality, reducing the incidence of device-related adverse events, and substantially increasing physician satisfaction. It holds great potential for clinical application.Keywords: otological surgery, checklist management, standard operating procedures, nursing quality, satisfaction, effectiveness